Use of Interactive Focus Cards in Educational Learning Pancasila for Class 1 Elementary School Students - Widyaningsih, Diah; Aryani, Ine Kusuma (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to improve the learning focus of grade 1 students of SDN 2 Pamijen Baturraden through innovative media in the form of interactive focus cards. The lack of focus behavior that commonly occurs in early childhood students is caused by internal factors such as immature cognitive development, as well as external factors such as a less supportive learning environment. Interactive focus cards are designed to overcome this problem by combining visual, tactical, and game elements to attract attention and increase student engagement. The study used a qualitative approach, conducted during four meetings with 20 students as subjects. The results of the study are expected to describe the effectiveness of this media in improving learning concentration and becoming an innovative alternative for teachers. In addition, this media integrates 21st century educational values such as critical thinking (HOTS), collaboration, and communication. It is hoped that this study will contribute to improving the quality of learning and become a reference for similar research in the future.